ANALISIS MULTI OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANAYSIS (MOORA) DALAM MODEL REKOMENDASI EKSTRAKURIKULER SISWA - Idaman, Akbar; Zarkasyi, Muhammad Imam; Aurlani, Febry; Arahman, Hamjah (Smart Education, 2025)
Abstract: This research applies the Multi Objective Optimization On the Basis of Ratio Analysis (MOORA) method to determine the appropriate extracurricular activity recommendations at XYZ School, aiming to facilitate data-driven decision-making in selecting extracurricular activities that align with students' interests and talents. The methodology includes data collection through observation and interviews, followed by the application of the MOORA method to process data on students' interests, talents, creativity, and potential involvement in extracurricular activities. The results show that the application of the MOORA method produces objective and systematic rankings of the available extracurricular activities based on the established criteria. The Scouting activity, with the highest value (Yi = 0.4821), was found to be the most suitable activity for students' profiles, followed by Arts and Paskibra. The MOORA method proves effective in providing more accurate and efficient extracurricular activity recommendations, addressing issues in previous subjective and ad-hoc decision-making processes. This study concludes that the application of MOORA can enhance the quality of decisions in selecting extracurricular activities, potentially enriching students' experiences and skill development.Keyword: MOORA; Extracurricular recommendations; Decision-making; Decision support system; Education.Abstrak: Penelitian ini mengaplikasikan metode Multi Objective Optimization On the Basis of Ratio Analysis (MOORA) untuk menentukan rekomendasi kegiatan ekstrakurikuler yang tepat di Sekolah XYZ, dengan tujuan untuk mempermudah pengambilan keputusan berbasis data mengenai kegiatan ekstrakurikuler yang sesuai dengan minat dan bakat siswa. Metodologi penelitian ini melibatkan pengumpulan data melalui observasi dan wawancara, serta penerapan metode MOORA untuk mengolah data mengenai minat, bakat, kreativitas, dan potensi keterlibatan siswa dalam kegiatan ekstrakurikuler. Hasil penelitian menunjukkan bahwa penerapan metode MOORA dapat menghasilkan peringkat yang objektif dan sistematis terhadap kegiatan ekstrakurikuler yang tersedia, berdasarkan kriteria yang ditetapkan. Kegiatan Pramuka, dengan nilai tertinggi (Yi = 0,4821), dinilai sebagai kegiatan yang paling sesuai dengan profil minat dan bakat siswa, diikuti oleh Kesenian dan Paskibra. Metode MOORA terbukti efektif dalam memberikan rekomendasi kegiatan ekstrakurikuler yang lebih tepat dan efisien, mengatasi masalah pemilihan yang sebelumnya bersifat subjektif dan ad-hoc. Penelitian ini menyimpulkan bahwa penerapan MOORA dapat meningkatkan kualitas keputusan dalam pemilihan kegiatan ekstrakurikuler, yang berpotensi memperkaya pengalaman dan pengembangan keterampilan siswa.Kata kunci: MOORA; Rekomendasi ekstrakurikuler; Pengambilan keputusan; Sistem pendukung keputusan; Pendidikan.